2023
DOI: 10.1021/acsnano.2c10736
|View full text |Cite
|
Sign up to set email alerts
|

Chemiresistive Hydrogen Sensing with Size-Limited Palladium Nanoparticles in Iptycene-Containing Poly(arylene ether)s

Abstract: Metal nanoparticles have been widely employed in chemical sensing due to their high reactivity toward various gases. The size of the metal nanoparticles often dictates their reactivity and hence their performance as chemiresistive sensors. Herein, we report that iptycene-containing poly-(arylene ether)s (PAEs) have been shown to limit the growth of palladium nanoparticles (Pd NPs) and stabilize the Pd NPs dispersion. These porous PAEs also facilitate the efficient transport of analytes. Single-walled carbon na… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 49 publications
0
5
0
Order By: Relevance
“…For example, sensors made from Pd nanoparticle-decorated CNT ropes are 20–30 times more sensitive to H 2 and respond six times faster than pure Pd nanowires . The dominant carbon-based sensing mechanism exploits the fact that pristine CNTs (or graphene) are generally p-doped by chemisorbed oxygen under ambient conditions. When a Pd-functionalized CNT or graphene sheet is exposed to H 2 , electrons are transferred from the α-PdH x nanoparticles into the CNT π-network, decreasing the number of carrier holes and increasing the resistance …”
Section: Carbon Sensorsmentioning
confidence: 99%
“…For example, sensors made from Pd nanoparticle-decorated CNT ropes are 20–30 times more sensitive to H 2 and respond six times faster than pure Pd nanowires . The dominant carbon-based sensing mechanism exploits the fact that pristine CNTs (or graphene) are generally p-doped by chemisorbed oxygen under ambient conditions. When a Pd-functionalized CNT or graphene sheet is exposed to H 2 , electrons are transferred from the α-PdH x nanoparticles into the CNT π-network, decreasing the number of carrier holes and increasing the resistance …”
Section: Carbon Sensorsmentioning
confidence: 99%
“…45,46 It is expected that inducing ferromagnetism in In 2 O 3 will increase the possibility of getting enhanced paramagnetic NO 2 gas sensing responses under the influence of an external magnetic field. 25,26 Ferromagnetism in In 2 O 3 can be induced by introducing vacancies, 47,48 by nanoconfinement effects 49,50 or by doping magnetic species. 46,51 Doping ferromagnetic species should be a much easier, certain, and straightforward way to induce ferromagnetism in In 2 O 3 than creating suitable vacancies or nanostructures.…”
Section: Introductionmentioning
confidence: 99%
“…Among various MOSs, In 2 O 3 (Figure ) is a promising chemiresistive NO 2 sensor. Pristine In 2 O 3 is a diamagnetic material. , It is expected that inducing ferromagnetism in In 2 O 3 will increase the possibility of getting enhanced paramagnetic NO 2 gas sensing responses under the influence of an external magnetic field. , Ferromagnetism in In 2 O 3 can be induced by introducing vacancies, , by nanoconfinement effects , or by doping magnetic species. , Doping ferromagnetic species should be a much easier, certain, and straightforward way to induce ferromagnetism in In 2 O 3 than creating suitable vacancies or nanostructures. In this work, ferromagnetism has been induced in In 2 O 3 by doping ferromagnetic elements Co, Ni, and Fe.…”
Section: Introductionmentioning
confidence: 99%
“…To enhance this chemiresistive response in metal-functionalized SWCNTs, it is essential to construct a robust interface with strong electronic coupling between metal complexes and SWCNTs. We have previously shown that pentiptycene-based conjugated polymers, such as P4 in Figure a, effectively bind and disperse small diameter SWCNTs in organic solvents and significantly improve their sensing performance. , To expand the functionalities of these SWCNT binding polymers to include transition metals, we have introduced metal chelation sites in the backbone (Figure a). Contrary to other polymer-wrapped SWCNTs, where metal species are anchored by pendant functional groups that are not necessarily in direct communication with the SWCNTs, the metal species chelated to the backbone of these pentiptycene polymers are positioned to interact directly with the graphene sidewalls of SWCNTs (Figure b).…”
Section: Introductionmentioning
confidence: 99%
“…The rigid pentiptycene units in these polymers also produce internal free volume to create porous interstitial cavities. These iptycene-based porous nanostructures are conducive to gas analyte diffusion and have shown to facilitate the analyte-selector interactions in gas sensing. ,, The solution processability of the resulting pentiptycene polymer/SWCNT complexes also provides a practical and scalable sensor fabrication. More importantly, this modular platform enables rapid sensor screening to identify the optimal transition-metal-based selectors for sensors of specific needs.…”
Section: Introductionmentioning
confidence: 99%